Pengaruh Penerapan Akuntansi Pertanggunjawaban Terhadap Prestasi Kerja Pada PT. Telkom Padang Wilayah Sumatera Barat - Amalia Afdha; Fitra Oliyan (Akuntansi dan Manajemen, 2017)
This study aims to examine the effect of accounting accountability on work performance. The research population is all employees working at PT. Telkom Padang West Sumatra Region. Data collection methods used were questionnaires and interviews. The sample used for the questionnaire was 50 respondents with a purposive sampling method. Interviews were conducted with Officer 1 part of the Cash Bank at PT. Telkom Padang West Sumatra Region. The data analysis technique uses simple regression analysis with the help of SPSS version 20. Based on hypothesis testing, accountability accounting has a significant effect on work performance. From additional information obtained by researchers through interviews, researchers found that the company has implemented a good accountability accounting that can be known from the fulfillment of all requirements for the implementation of accountability accounting, namely organizational structure, budget, cost classification, accounting system, and cost reporting system.